Oppositional Effects of Serotonin Receptors 5-HT1a, 2, and 2c in the Regulation of Adult Hippocampal Neurogenesis - Klempin, Friederike; Babu, Harish; De Pietri Tonel, Davide; Alarcon, Edson; Fabel, Klaus; Kempermann, Gerd (Frontiers in Molecular Neuroscience, 2010)
Serotonin (5-HT) appears to play a major role in controlling adult hippocampal neurogenesis and thereby it is relevant for theories linking failing adult neurogenesis to the pathogenesis of major depression and the mechanisms of action of antidepressants. Serotonergic drugs lack acute effects on adult neurogenesis in many studies, which suggests a surprising long latency phase. Here we report that the selective serotonin reuptake inhibitor fluoxetine, which has no acute effect on precursor cell proliferation, causes the well-described increase in net neurogenesis upon prolonged treatment partly by promoting the survival and maturation of new postmitotic neurons. We hypothesized that this result is the cumulative effect of several 5-HT-dependent events in the course of adult neurogenesis. Thus, we used specific agonists and antagonists to 5-HT1a, 2, and 2c receptor subtypes to analyze their impact on different developmental stages. We found that 5-HT exerts acute and opposing effects on proliferation and survival or differentiation of precursor cells by activating the diverse receptor subtypes on different stages within the neuronal lineage in vivo. This was confirmed in vitro by demonstrating that 5-HT1a receptors are involved in self-renewal of precursor cells, whereas 5-HT2 receptors effect both proliferation and promote neuronal differentiation. We propose that under acute conditions 5-HT2 effects counteract the positive proliferative effect of 5-HT1a receptor activation. However, prolonged 5-HT2c receptor activation fosters an increase in late stage progenitor cells and early postmitotic neurons, leading to a net increase in adult neurogenesis. Our data indicate that serotonin does not show effect latency in the adult dentate gyrus. Rather, the delayed response to serotonergic drugs with respect to endpoints downstream of the immediate receptor activity is largely due to the initially antagonistic and un-balanced action of different 5-HT receptors.